2020
DOI: 10.3390/su12051835
|View full text |Cite
|
Sign up to set email alerts
|

Using a Citizen Science Approach with German Horse Owners to Study the Locomotion Behaviour of Horses on Pasture

Abstract: Engaging farmers as citizen scientists may be a cost-efficient way to answering applied research questions aimed at more sustainable land use. We used a citizen science approach with German horse farmers with a dual goal. Firstly, we tested the practicability of this approach for answering 'real-life' questions in variable agricultural land-use systems. Secondly, we were interested in the knowledge it can provide about locomotion of horses on pasture and the management factors influencing this behaviour. Out o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This nding is similar to the research results of community-based rainfall monitoring in Nepal byDavids et al (2019). Unlike developing countries, in developed countries such as Germany and Italy, citizen science programs access citizens through unions, agencies, mass media(Pernat et al, 2021;Scaini et al, 2021;Schmitz et al, 2020), or individual invitations via email(Phillips et al, 2019…”
supporting
confidence: 84%
“…This nding is similar to the research results of community-based rainfall monitoring in Nepal byDavids et al (2019). Unlike developing countries, in developed countries such as Germany and Italy, citizen science programs access citizens through unions, agencies, mass media(Pernat et al, 2021;Scaini et al, 2021;Schmitz et al, 2020), or individual invitations via email(Phillips et al, 2019…”
supporting
confidence: 84%
“…This finding is similar to the research results of community-based rainfall monitoring in Nepal by Davids et al ( 2019 ). Unlike developing countries, in developed countries such as Germany and Italy, citizen science programs access citizens through unions, agencies, mass media (Pernat et al, 2021 ; Scaini et al, 2021 ; Schmitz et al, 2020 ), or individual invitations via email (Phillips et al, 2019 ). We assume that participants feel safe when they are informed about citizen science programs by friends and relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Restrictions in pasture access bear additional negative effects in the form of rebound behaviors. For example, Schmitz et al [59] found that horses increase running and trampling on pasture with decreasing grazing duration. Consequently, the stress on grass swards increases and poses a challenge to sustainable grassland management.…”
Section: Nitrogen Surplus and The Linkage To "Turnout"mentioning
confidence: 99%
“…We found tendentially higher nitrogen surpluses on turnout areas of single-housed horses compared with turnout areas of group-housed horses, suggesting that group housing of horses may support a better paddock and pasture management due to the generally integrated turnout areas (e.g., daily demanuring) and thereby reduce excretions of the horses in the soil. Schmitz and Isselstein [59] also pointed out the potential of free-range stabling (i.e., active stables, paddock trails), as opposed to box-stall stabling, to enable sustainable grazing management. However, when the space allowance per horse is taken into account, the effect of housing system vanishes.…”
Section: Nitrogen Surplus and The Linkage To "Turnout"mentioning
confidence: 99%
See 1 more Smart Citation